REFORMULASI TINDAK PIDANA ZINA DALAM RUU KUHP INDONESIA DAN SUMBANGAN HUKUM ISLAM TERHADAP-NYA - Zul Anwar Ajim (Yurisprudentia: Jurnal Hukum Ekonomi, 2019)
This paper begins with a fact that the presence of Islamic law in the Indonesian legal system if the terms of the theory of existence proves that Islamic law actually become a source of material for the rule of law in Indonesia legislation with some form as the provisions of the theory. The fact is solely to respond to the development of science and the progress of time. This paper is focused on the formulation of the Bill Criminal Code provisions on the crime of adultery, and highlights the contribution of Islamic criminal law against him. From the search for the sources are found, that the formulation of the crime of adultery in the Draft Bill is found that that provision is derived from the Islamic legal code that is submitted through the results of a seminar held Islamic jurists. This fact proves that Islamic law becomes material for the formation of a national law. It can be concluded that Islamic law be a source of national law.